2013
DOI: 10.1007/s11207-012-0220-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic and Long-Term Variation of Sunspot Magnetic Fields

Abstract: Measurements from the Mount Wilson Observatory (MWO) are used to study the long-term variations of sunspot field strengths from 1920 to 1958. Following a modified approach similar to that in Pevtsov et al. (2011), for each observing week we select a single sunspot with the strongest field strength measured that week and then compute monthly averages of these weekly maximum field strengths. The data show the solar cycle variation of the peak field strengths with an amplitude of about 500-700 gauss (G), but no s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 6 publications
(18 reference statements)
5
52
0
3
Order By: Relevance
“…A set of unbiased measurements of umbral contrast indicates that umbral contrast has not been decreasing with time, but has remained constant (Leonard and Choudhary, 2008;de Toma et al, 2013). This is consistent with the results of Pevtsov et al (2014), who found no significant long-term trend in the maximum sunspot magnetic-field strength. Another complication is suggested by the finding that the relation between spot number and F 10.7 flux has been changing (Livingston, Penn, and Svalgaard, 2012) while the relation between F 10.7 and sunspot area (de Toma et al, 2013) and F 10.7 magnetic indices (Henney et al, 2012) has remained the same.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A set of unbiased measurements of umbral contrast indicates that umbral contrast has not been decreasing with time, but has remained constant (Leonard and Choudhary, 2008;de Toma et al, 2013). This is consistent with the results of Pevtsov et al (2014), who found no significant long-term trend in the maximum sunspot magnetic-field strength. Another complication is suggested by the finding that the relation between spot number and F 10.7 flux has been changing (Livingston, Penn, and Svalgaard, 2012) while the relation between F 10.7 and sunspot area (de Toma et al, 2013) and F 10.7 magnetic indices (Henney et al, 2012) has remained the same.…”
Section: Discussionsupporting
confidence: 86%
“…The average cycle maximum in sunspot number for Cycles 22, 23, and 24 is about 150, 110, and 60, respectively (www.sidc.oma.be). On the other hand, Pevtsov et al (2014) concluded from a detailed study of sunspot magnetic fields that there has been no secular decline in the maximum magnetic field strength in sunspots, except perhaps during the last few minima. The decline in peak activity could be part of a longer-term cycle such as the Gleissberg cycle (Gleissberg, 1967;Usoskin and Mursula, 2003;Mouradian, 2013;McCracken et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…If a global dipolar field exists and reverses direction, this may be detectable by temporal changes in the cutoff frequency of the radio emission over month-to-year long timescales. For example, the annual averages of sunspot magnetic field strengths vary in accordance with the solar cycle, with stronger fields at solar maximum that then decline until solar minimum, when magnetic reversal occurs (Pevtsov et al 2014). A study of the monthly mean total stellar radio flux offers another means of assessing the presence of activity cycles in brown dwarfs, as this quantity varies in a prominent way during the solar activity cycle for 1-9.6 GHz frequencies (Shibasaki 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Livingston et al (2006) and Penn & Livingston (2011) found that the field strength of sunspots was stronger at the beginning of cycle 22 than at its end. Rezaei et al (2012), Pevtsov et al (2014), and Schad (2014) reported a cyclic variation of the field strength, but found no significant trace of a longterm variation in their data. Livingston et al (2012) predicted a monotonic decrease of sunspot field strength that should lead to the disappearance of sunspots in cycle 25.…”
Section: Introductionmentioning
confidence: 95%